Anti-neuroinflammatory therapy for non-pulsatile tinnitus in patients with sinus vascular anomalies: preliminary result on two cases - Di Stadio, Arianna; Messineo, Daniela; Indovina, Iole; Motta, Giovanni; Ralli, Massimo; Brenner, Michael J. (Frontiers in Neurology, 2025)
BackgroundVascular anomalies are commonly associated with pulsatile tinnitus, but their potential role in triggering non-pulsatile tinnitus through neuroinflammation is not well established. Furthermore, few studies have investigated non-pulsatile tinnitus associated with altered cerebrovascular supply and whether anti-neuroinflammatory therapy might alleviate symptoms.Materials and methodsWe describe two patients presenting with non-pulsatile tinnitus and sigmoid sinus stenosis confirmed by imaging, with other causes systematically excluded.ResultsMagnetic resonance venography demonstrated severe stenosis of the transverse and sigmoid sinuses, alongside compensatory ipsilateral vascular dilatation. These structural abnormalities suggested disrupted venous blood flow, contributing to the neuroinflammatory processes associated with non-pulsatile tinnitus. Following treatment with an anti-inflammatory molecule, both patients reported a substantial reduction in tinnitus severity.ConclusionThis study supports the potential of anti-inflammatory treatments in managing non-pulsatile tinnitus linked to sinus vascular anomalies. Further research is warranted to elucidate these relationships and confirm therapeutic efficacy of anti-inflammatory agents.